Propofol Ameliorates ox-LDL-Induced Endothelial Damage Through Enhancing Autophagy via PI3K/Akt/m-TOR Pathway: A Novel Therapeutic Strategy in Atherosclerosis - Zhou, Hongyi; Jiang, Fan; Leng, Yufang (Frontiers in Molecular Biosciences, 2021)
Objective: Atherosclerosis (AS) represents a common age-associated disease, which may be accelerated by oxidized low-density lipoprotein (ox-LDL)-induced endothelial cell injury. This study aimed to investigate the effects of Propofol on ox-LDL-induced endothelial damage and the underlying molecular mechanisms. Methods: Human umbilical vein endothelial cells (HUVECs) were exposed to ox-LDL to induce endothelial damage. HUVECs were pretreated with 0, 5, 25 and 100 μM Propofol, followed by exposure to 100 μg/mL ox-LDL for 24 h. Cell viability was assessed by cell counting kit-8 (CCK-8) assay. The expression of autophagy- and apoptosis-related proteins was detected via western blot. Autophagosome was investigated under a transmission electron microscope. After co-treatment with autophagy inhibitor Bafilomycin A1 or si-Beclin-1, cell apoptosis was detected by flow cytometry. Furthermore, under cotreatment with PI3K activator 740Y-P, PI3K/Akt/m-TOR pathway- and autophagy-related proteins were examined by western blot. Results: With a concentration-dependent manner, Propofol promoted the viability of HUVECs exposed to ox-LDL, and increased LC3-II/I ratio and Beclin-1 expression, and decreased P62 expression. The formation of autophagosome was enhanced by Propofol. Furthermore, Propofol treatment elevated Bcl-2/Bax ratio and lowered Caspase-3 expression. Bafilomycin A1 or si-Beclin-1 distinctly ameliorated the inhibitory effects of Propofol on apoptosis in ox-LDL-exposed HUVECs. Moreover, Propofol lowered the activation of PI3K/Akt/m-TOR pathway in HUVECs under exposure to ox-LDL. However, its inhibitory effects were weakened by 740Y-P. Conclusion: Collectively, this study revealed that Propofol could ameliorate ox-LDL-induced endothelial damage through enhancing autophagy via PI3K/Akt/m-TOR pathway, which might offer a novel therapeutic strategy in AS.